2020
DOI: 10.1088/1361-648x/abc4cb
|View full text |Cite
|
Sign up to set email alerts
|

Charge affinity and solvent effects in numerical simulations of ionic microgels

Abstract: Ionic microgel particles are intriguing systems in which the properties of thermo-responsive polymeric colloids are enriched by the presence of charged groups. In order to rationalize their properties and predict the behaviour of microgel suspensions, it is necessary to develop a coarse-graining strategy that starts from the accurate modelling of single particles. Here, we provide a numerical advancement of a recently-introduced model for charged co-polymerized microgels by improving the treatment of ionic gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 56 publications
5
19
0
Order By: Relevance
“…This result can be rationalized by considering the electric charge brought by initiator molecules. Indeed, in agreement with previous studies on charged microgels ( 33 , 39 ), a shift of to higher values is found when the amount of charges increases. In addition, we observe that, for all studied samples, the VPT transition is encountered at a lower temperature, by 1.0 C, for with respect to .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This result can be rationalized by considering the electric charge brought by initiator molecules. Indeed, in agreement with previous studies on charged microgels ( 33 , 39 ), a shift of to higher values is found when the amount of charges increases. In addition, we observe that, for all studied samples, the VPT transition is encountered at a lower temperature, by 1.0 C, for with respect to .…”
Section: Resultssupporting
confidence: 92%
“…In all cases, the decrease of at the minimum is also accompanied by its decrease at small , indicating that the growth of is not compensated by that of under swollen conditions. At large , most curves tend to recover the HS value, except for the most charged microgels, which are expected to completely collapse at much larger effective temperatures ( 33 , 39 ), beyond those explored in the present simulations.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations